Observational constraints in nonlocal gravity: the Deser-Woodard case - Amendola, Luca; Nersisyan, Henrik (Arxiv, 2019)
We study the cosmology of a specific class of nonlocal model of modified gravity, the so-called Deser-Woodard (DW) model, modifying the Einstein-Hilbert action by a term $\sim R f(\Box^{-1}R)$, where